The moduli space of left-invariant metrics on six-dimensional characteristically solvable nilmanifolds - Cardoso, Isolda Eugenia (2024)
A real Lie algebra is said to be characteristically solvable if its derivation algebra is solvable. We explicitly determine the moduli space of left-invariant metrics, up to isometric automorphism, for 6-dimensional nilmanifolds whose associated Lie algebra is characteristically solvable. We also compute the corresponding full isometry groups. For each left-invariant metric on these nilmanifolds we compute the index and distribution of symmetry. In particular, we find the first known examples of Lie groups which do not admit a left-invariant metric with positive index of symmetry. As an application we study the index of symmetry of nilsoliton metrics on characteristically solvable Lie algebras. We prove that nilsoliton metrics detect the existence of left-invariant metrics with positive index of symmetry.